The Bush effect : polarization, turnout, and activism in the 2004 Presidential Election - Abramowitz, Alan I.; Stone, Walter J. (2006)
Contiene bibliografía
Keywords: 2004; Elecciones presidenciales; Comportamiento electoral; Estados Unidos